2011
DOI: 10.1002/cncr.26617
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput genotyping in osteosarcoma identifies multiple mutations in phosphoinositide‐3‐kinase and other oncogenes

Abstract: Background Identification of new genes that are mutated in osteosarcomas is critical to developing a better understanding of the molecular pathogenesis of this disease and discovering new targets for therapeutic development. Methods We identified somatic non-synonymous coding mutations in oncogenes associated with human cancers and hotspot mutations from tumor suppressor genes that were either well-described in literature or seen multiple times in human cancer sequencing efforts. We then systematically chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 47 publications
2
39
1
Order By: Relevance
“…Non-translocationrelated sarcomas can be further grouped as sarcomas with a simple genetic profile based on limited amplifications, such as dedifferentiated liposarcomas and parosteal OS (10,11), and major sarcomas with extremely complex genomic imbalances, such as leiomyosarcomas, undifferentiated pleomorphic sarcomas, pleomorphic liposarcomas and conventional OS (12). In conventional OS, these genomic aberrations cause oncogenic changes in such diverse processes as cell cycle regulation, cell death/cytokine pathways, proliferative signaling pathways, telomere dysfunction, metastasis and tumor suppression (13)(14)(15)(16)(17)(18)(19)(20). Recently, several studies have revealed that the PI3K-mTOR pathway is crucial in conventional OS (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-translocationrelated sarcomas can be further grouped as sarcomas with a simple genetic profile based on limited amplifications, such as dedifferentiated liposarcomas and parosteal OS (10,11), and major sarcomas with extremely complex genomic imbalances, such as leiomyosarcomas, undifferentiated pleomorphic sarcomas, pleomorphic liposarcomas and conventional OS (12). In conventional OS, these genomic aberrations cause oncogenic changes in such diverse processes as cell cycle regulation, cell death/cytokine pathways, proliferative signaling pathways, telomere dysfunction, metastasis and tumor suppression (13)(14)(15)(16)(17)(18)(19)(20). Recently, several studies have revealed that the PI3K-mTOR pathway is crucial in conventional OS (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In conventional OS, these genomic aberrations cause oncogenic changes in such diverse processes as cell cycle regulation, cell death/cytokine pathways, proliferative signaling pathways, telomere dysfunction, metastasis and tumor suppression (13)(14)(15)(16)(17)(18)(19)(20). Recently, several studies have revealed that the PI3K-mTOR pathway is crucial in conventional OS (15,16). However, the result of a clinical study of the mTOR inhibitor in OS treatment was unsatisfactory (21).…”
Section: Introductionmentioning
confidence: 99%
“…AKT prevents apoptosis by activating anti-apoptotic signals through phosphorylating glycogen synthase kinase 3 (GSK3), Bad and caspase-9 and through activating transcriptional factors, such as forkhead (FOXO-1) and NF-kappa B (Yu et al, 2006;Cardone et al, 1998;Brunet et al, 1999;Romashkova et al, 1999). In addition, abnormal function of the PI3K/AKT pathway has been reported in many human tumors (Roy et al, 2002), including the OSA developed by PI3KCA gene mutation (Choy et al, 2012) and this signal pathway has been suggested to be a potential target for cancer chemotherapy. Suppressing the phosphorylation of Akt and its substrates FOXO transcription factor and GSK3 in OSA cells cause the suppression of proliferation and induction of mitochondria-and caspase-dependent apoptosis, induced the release of cytochrome c accompanied by activation of caspase-9, caspase-3 and cleavage of poly (ADP-ribose) polymerase (PARP) ( Jin et al, 2007).…”
Section: Down Regulation Of Pi3k/akt Pathway Induce Anoikis Of Osa Cellsmentioning
confidence: 99%
“…35 This panel has been optimized and refined during several years, and has demonstrated utility in profiling a wide variety of rare and common cancers for mutational events, regardless of the site of origin of the cancer. [36][37][38][39][40] Using our current panel of OncoMap, comprising 439 assays designed to detect 471 unique mutations in 41 cancer genes (Table 1), we interrogated 244 lung adenocarcinomas. Anonymized tumor specimens were obtained from the Cooperative Human Tissue Network, the Dana-Farber Cancer Institute, and the clinical archives of the departments of pathology at Brigham and Women's Hospital, Boston, Massachusetts.…”
Section: Oncomapmentioning
confidence: 99%